CLINICAL PATHOGENETIC SUBSTANTIATION OF THE REGENERATIVE TREATMENT OF PARTURIENTS WHO SUFFERED FROM OBSTETRICAL HAEMORRHAGES - Herasymenko, Svitlana; Nikitina, Iryna; Smiian, Svetlana (Eastern Ukrainian Medical Journal, 2023)
The publication is devoted to an urgent problem of modern obstetrics – the study of pathophysiological changes in the organism of parturients after obstetrical haemorrhages, improvement of restorative treatment, as well as reduction of complications in the puerperium and prevention of their occurrence.The aim of the study: to increase the effectiveness of restorative treatment of women in labor who suffered obstetric bleeding by studying the features of the clinical course, mechanisms of pathogenetic disorders, and their correction using ozone therapy.Materials and methods. A comprehensive clinical and laboratory examination of 150 women in labor was carried out, including 120 women (the main group) who suffered bleeding during childbirth and the early postpartum period. The control group consisted of 30 women with the physiological course of labor, childbirth and the early postpartum period. The state of lipid peroxidation (LPO) in parturient women was evaluated by the content of primary lipid products in the blood plasma – diene conjugates (DK) according to the method of B.V. Gavrilov (1983) and secondary molecular products – malondialdehyde (MDA) using the reaction with 2‑thiobarbituric acid. The activity of the enzymatic link of the antioxidant system (AOS) was determined by the content of catalase in peripheral blood erythrocytes using the substrate hydrogen peroxide and glutathione peroxidase (GPO) using the P‑phenylenediamine substrate. The Spielberg–Hanin scale of state and trait anxiety was used to study the state of the psycho-emotional sphere in parturient women. Morphological examination of preparations of placentas and surgically removed uteri was carried out with staining of sections with hematoxylin and eosin, picrofuchsin according to Van Gieson.Results. Basic etiopathogenetic factors of the development of obstetric haemorrhages were examined, changes in the psychoemotional status of the patients were detected, haematological and metabolic indices, parameters of oxidation-antioxidation homeostasis and endogenic intoxication were studied, as well as morphofunctional disorders in placentas and uteruses. The efficacy of the restorative treatment of the parturients, who had moderate and massive haemorrhages during delivery, with the use of medical ozone in combined treatment versus traditional methods of treatment was studied.Conclusion. From the first day of the puerperium, free-radical lipid peroxidation increases, the activity of the enzymatic and non-enzymatic links of the antioxidant system increases, endogenous intoxication increases, and lactate and pyruvate levels increase. In the placentas of women in labor who suffered bleeding during labor, there is a violation of the synthesis of type IV collagen in the basal membranes of vessels and the phenomenon of endothelial dysfunction in the form of increased expression of endothelin by the endotheliocytes of the vessels of the decidual membrane (53.8 ± 2.9 µa) and the villous chorion (46.0 ± 2.6 μa). In the uterus, an increase in the expression of endothelin by endotheliocytes of the spiral arteries of the uterus (57.8 ± 8.56 µa) was detected, in combination with a violation of the synthesis of stromal collagen of type I and III and type IV in the basal membranes of vessels.